Increased spontaneous neuronal activity in structurally damaged cortex is correlated with early motor recovery in patients with subcortical infarction. (9th October 2015) - Liu, G.; Dang, C.; Peng, K.; Xie, C.; Chen, H.; Xing, S.; Chen, X.; Zeng, J.
Abstract : Background and purpose: Secondary cortical thinning and volumetric atrophy in the motor‐related cortex can inhibit early functional recovery after subcortical infarction. However, the relationship between the spontaneous neuronal activity in these cortices and motor recovery in patients with focal cerebral infarct remains unknown. Methods: Structural magnetic resonance imaging (MRI) and resting‐state functional MRI were conducted 1, 4 and 12 weeks after onset in 22 patients with an acute subcortical infarct and in 22 normal subjects. Group differences in cortical thickness and in the amplitude of low‐frequency fluctuation (ALFF) in motor‐related areas were evaluated, and the relationships between ALFF, cortical thickness changes and changes in the Fugl−Meyer scores of physical performance were further analyzed. Results: In patients with subcortical infarction, progressively decreasing cortical thickness was found over the observation period ipsilesionally in the primary motor cortex (PMC), supplementary motor cortex (SMC) and precuneus (all P < 0.05). Contralesionally, progressive increases in cortical thickness were detected in SMC and insula (all P < 0.05). Increases in ALFF were observed only in PMC (bilaterally) and only at 12 weeks after stroke (all P < 0.05). The cortical thickness changes in the contralesional SMC ( r s = 0.483, P = 0.023) and the ALFF changes in bilateral PMC (ipsilesional, r s = 0.51, P = 0.015; contralesional, r s = 0.463, P = 0.03) were positively correlated with changes in the Fugl−Meyer scores. Conclusions: These results suggest that increased spontaneous neuronal activity of the PMC, a region structurally damaged secondarily to ischaemic lesion, may contribute to early motor recovery in patients with subcortical infarction.